PENGEMBANGAN E-MODUL PEMBELAJARAN MATEMATIKA BERBASIS ETNOMATEMATIKA BETAWI PADA MATERI BANGUN DATAR KELAS IV MI/SD - Suryaningsih, Tri; Putriyani, Ihda Juita (JMIE (Journal of Madrasah Ibtidaiyah Education), 2022)
This research was conducted with the aim of developing teaching materials in the form of electronic modules based on Betawi culture both in material content and in presentation. The method of research is Research and Development (R&D) with the type of research is the 4-D (Four-D)Â  The results showed that the e-module developed met the appropriate criteria based on the assessment of 6 validators on aspects including aspects of the content of the material, presentation, conformity of e-modules with the concept of Ethnomatematics, effectiveness of media on learning strategies, physical appearance, and language. Then the students' responses to the e-module showed a positive response with very good criteria based on sample assessment on the aspects of e-module display, presentation and interest